Effectiveness of Automated External Defibrillator Drones for Handling Out-Of-Hospital Cardiac Arrest (OHCA): Literature Review - Nurhayati, Nurhayati; Roswita, Ria (Poltekkes Kemenkes Semarang, 2024)
Background: Out-of-hospital cardiac arrest is one of the leading causes of death worldwide. Out-of-hospital cardiac arrest or OHCA represents a significant burden of disease globally. The number of out-of-hospital cardiac arrests reaches 360,000 events every year. Treatment for cardiac arrest requires immediate defibrillation to increase the survival rate of OHCA patients. One method that can be used is by sending AEDs using drones. It is hoped that sending and using AEDs via drones can increase the rate of AED application and reduce defibrillation time.Methods: This study is a literature review which aims to determine the effectiveness of AED drones for treating out-of-hospital cardiac arrest (OHCA). This literature review analyzes 10 articles originating from journal databases, namely Google Scholar, Pubmed and Science Direct with the keywords